Arte Programmata : Freedom, Control, and the Computer in 1960s Italy - Caplan, Lindsay, 1980- (Book collections on Project MUSE., 2022)
"In postwar Italy, a group of visionary artists used emergent computer technologies as both tools of artistic production and a means to reconceptualize the dynamic interrelation between individual freedom and collectivity. Arte Programmata traces the multifaceted practices of these groundbreaking artists and their conviction that technology could provide the conditions for a liberated social life"--